2018
DOI: 10.3390/ph11030077
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Protective Effect of Oligoribonucleotides-d-Mannitol Complexes against Thioacetamide-Induced Hepatotoxicity in Mice

Abstract: This study investigated the potential hepatoprotective effect of oligoribonucleotides-d-mannitol complexes (ORNs-d-M) against thioacetamide (TAA)-induced hepatotoxicity in mice. The hepatoprotective activity of ORNs-d-M was evaluated in thioacetamide (TAA)-treated C57BL/6J. Results indicate that treatment with ORNs-d-M displayed a protective effect at the TAA-induced liver injury. Treatment with ORNs-d-M, starting at 0 h after the administration of TAA, decreased TAA-elevated serum alanine aminotransferase (AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…The preventive capacity of AE-EOP and AAE-EOP might be correlated to their bioactive molecule content. Similar results in other animal models have been reported previously, which revealed the possible stabilization of the structural integrity of the liver cell membrane by bioactive molecules, including mannitol, 12 hydroxytyrosol, 13 and its derivative oleuropein. 40 Data from the literature have linked liver injury development to oxidative stress.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The preventive capacity of AE-EOP and AAE-EOP might be correlated to their bioactive molecule content. Similar results in other animal models have been reported previously, which revealed the possible stabilization of the structural integrity of the liver cell membrane by bioactive molecules, including mannitol, 12 hydroxytyrosol, 13 and its derivative oleuropein. 40 Data from the literature have linked liver injury development to oxidative stress.…”
Section: Discussionsupporting
confidence: 90%
“…11 Previous studies have demonstrated the protective effects of hydroxytyrosol and mannitol, as individual active molecules, against liver diseases. 12,13 Therefore, advances in the health benefits of extracts rich in hydroxytyrosol and mannitol could be useful in promoting functional and pharmaceutical formulations based on these natural compounds using EOP as a low cost bioresource. However, to the best of our knowledge, there is no available information on the in vivo effects of EOP extracts.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of NF-κB results in a significant enhancement of the genetic expression and overproduction of inflammatory cytokines, such as TNF-α and ILs. TNF-α is crucial for TAA-induced inflammation as it regulates the release of other proinflammatory mediators, such as IL-1β and NO, that complete the inflammatory response [ 48 , 49 , 50 ]. Our data are in the same line with the previous reports, as there was a significant enhancement of NF-κB p65 activation, as well as an increase in the level/genetic expression and protein immuno-expression of NF-κB/TNF-α in the TAA group.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant and inhibition of free radical production are important for the protection of cells from TAA-induced hepatotoxicity [43]. Different mechanisms, in which antioxidant compounds perform their scavenging properties, have been documented: They act as a physical barrier to prevent ROS generation, and they could access target biological sites, as a chemistry trap catching energy and chelating electrons; as a reactive species scavenging catalytic system and breaking redox chains, and scavenging radicals; or binding to targeted metal compounds and avoiding redox chain formation [44]. Most of them depend on the hydrogen atom transference rate from the compounds to the radicals [45].…”
Section: Discussionmentioning
confidence: 99%
“…EC + TAA showed a significant decrease in the serum levels of ALT and AST in relation with VE + TAA and TAA ( p ≤ 0.05). The results in EC + TAA are strongly related to the EC capacity to save the cell against necrotic damage produced by TAA to reduce the rate of transaminase release and cellular membrane stabilization [44].…”
Section: Discussionmentioning
confidence: 99%